The impact of motivation on employees performance: a study of private sector employees in small and medium enterprises (SME) within Klang Valley - Lee, Hui Le (2024)
This study examined the impact of motivation on employee performance in the service industry of private sector SME in Klang Valley, focusing on the relationship between various motivational factors and employee performance. This study used a descriptive cross-sectional research design, data were collected from 154 employees through questionnaires that addressed Maslow's hierarchy of needs and self-rated performance. Analysis revealed that Safety Needs had the highest impact on employee performance, followed by Esteem Needs, while Physiological Needs and Self-actualization Needs had moderate impacts, and Love and Belonging Needs had the least impact. Hypothesis testing showed a significant positive relationship only between Safety Needs and employee performance. Thus, addressing Safety Needs is crucial for enhancing employee performance in this sector.